Parallergic reactions to bovine tuberculin caused by Mycobacterium intracellulare - Langenegger, Jerome; Langenegger, Charlotte Hubinger; Ramos, Auvanir de Almeida (Pesquisa Agropecuaria Brasileira, 2014)
Three succesive tuberculinizations of a dairy herd of 325 animals revealed 27 (8.3%) positive reactors. This condition was recognized as parallergic sensitizations, considering the great variation in the tuberculin reactions with the same bovine, the weak intensity of these reactions and results of the comparative bovine and avian tuberculin test. The bovine’s pastures bordered the piggeries and the paddocks of an intensive pig breeding plant with about 2000 animals. The pigs waste (dung) was used to fertilize the soil of some lowland areas cultivated with forage to be given to the bovines, more intensily during the drier period from July to October. The mandibular lymphnodes of 164 slaughtered swines showed tuberculous-like lesions of 10.9% of the pigs and the bacteriological examination revealed mycobacterial infections of the Mycobacterium avium-intracellulare-scrofulaceum complex in 32.3% of the cases. Twelve calves infected by the subcutaneous, intradermal and oral route, with live or dead cultures of M. intracellulare isolated from the swines, induced parallegic sensitizations to bovine and avian tuberculin. The swine breeding plant, which is highly infected with the M. intracellulare, via the pigs’ waste, seems to be the source of infection and parallergic sensitizing of bovines.